Governance Strategy in Extracurricular Music Arts Learning at SMPN 3 Sindangkerta - Sigit Maulana; Jaeni Jaeni; Yahfanel Evi Fussalam (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Music extracurricular activities play a strategic role in supporting the development of talent, creativity, and character formation of students at the junior high school level. However, in practice, the implementation of these activities often faces various obstacles, both in terms of student learning motivation, learning methods, and unstructured governance systems. This study aims to describe the governance strategy for music extracurricular activities at SMPN 3 Sindangkerta, examining the learning methods applied. The study used a qualitative approach with descriptive methods. Data collection techniques included observation, interviews, and documentation studies. The results showed that the governance of music extracurricular activities was implemented through four main stages, namely planning, organizing, implementing, and evaluating. The learning methods applied included practice-based learning, project-based learning, and collaborative learning, which were considered relevant to the characteristics of junior high school students. This study concluded that the implementation of systematic and sustainable governance is essential to improve the quality and sustainability of music extracurricular activities in schools.